Therapeutic recreation camping programmes for children with chronic illnesses, and their siblings - Kiernan, Gemma Bridget (Trinity College (Dublin, Ireland). School of Psychology, 2001)
Within the healthcare system, camping programmes providing a form of therapeutic recreation service are emerging as a form of intervention for children with chronic illnesses, and their siblings. In numerous instances, American camping programmes have acted as a template for the development of European camping programmes. However, there is little information, especially within a European context, regarding the nature of these programmes, and a limited body of evidence regarding their effectiveness. Furthermore, research that has been conducted has tended to overlook the role that children, as the direct participants in these programmes, can play in providing feedback.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin